THE IMPACT OF ELECTRONIC ADVERTISEMENTS ON FINANCIAL SERVICES DEVELOPMENT IN JORDANIAN COMMERCIAL BANK - Al-Khalil, Waseem; Megdadi, Younes (International Journal of Marketing Research Innovation, 2022)
The study purpose is to examine the impact of electronic advertisements with their dimensions (advertising text, clarity of advertisement content, directing and technical design of the advertisement, and advertisement stimuli) on the development of banking services with their dimensions (technology used for services, quality of services, and diversity of services). The study methodology depend on the descriptive analysis approach used, and the study population covered all marketing department employees in the Jordanian commercial banks with a number of (409) employees, and the (SPSS) statistical program was used for hypothesis testing. The study concluded that there is a statistically significant effect at the level of significance (α≤0.05) for electronic advertisements with their combined dimensions (advertisement text, clarity of advertisement content, output and technical design of advertisement, and advertisement stimuli) in the development of banking services with its combined dimensions (technology used for services, quality of services, and diversity of services) for Jordanian commercial banks. The study findings suggest that the electronic advertisements are required including recorded videos that explain the nature of financial services within a clear content that highlights the benefits of those services and is designed and produced in technical ways within attractive stimuli for customers of Jordanian commercial banks.JEL Classification Codes: M30, M37.